Provision Of Learning Climate Formation In Madrasah Aliyah Environment - Jamrizal, Jamrizal; Afifah, Yuliana; Fikri, Ahmad; Atika, Atika; Azliani, Mayaza (Lembaga Dongan Dosen, 2025)
Community service conducted by the Islamic Education Management Study Program of UIN Sultan Thaha Saifuddin Jambi aims to improve teachers' understanding and skills in creating a conducive learning climate at the Laboratory Private Madrasah Aliyah, Jambi City. This study focuses on identifying problems that arise in the learning environment, such as the lack of physical comfort in the classroom, the lack of positive interaction between teachers and students, and the lack of understanding of the importance of learning climate in supporting students' academic and social development. As a solution, a training program was conducted by inviting 15 teachers to study and understand the concept of learning climate, its benefits, and techniques that can be applied to create a more comfortable and effective learning atmosphere. This training consisted of several sessions, including an introduction to the basic concept of learning climate, its benefits for the learning process, and interactive sessions such as group discussions and case studies. The evaluation results showed an increase in participants' understanding of the importance of creating a positive learning climate, as well as their readiness to apply these principles in daily teaching and learning activities. The program also identified several challenges that needed to be overcome, such as limited physical facilities and students' learning habits. Nevertheless, the program has succeeded in providing a positive impact in creating a more conducive learning environment, which is expected to improve the motivation and quality of student learning outcomes in madrasahs. The sustainability of this program is important to ensure a greater long-term impact on the development of education in madrasahs.